Immediate Treatment and Management of Extensive Facial Trauma in a Young Patient Following a Cycling Accident - Murai, Melissa K. [UNESP]; Delamura, Izabela F. [UNESP]; Sol, Izabella [UNESP]; da Costa, Monique G.; Magro Filho, Osvaldo [UNESP]; da Silva Fabris, André Luís [UNESP] (Wolters Kluwer, 2025)
Maxillofacial trauma treatment prioritizes airway patency, hemorrhage control, and rapid intervention to minimize negative outcomes. Complex avulsion of facial tissues represents a challenging clinical situation, leading to scar formation and aesthetic compromise. The main objective of this case report is to describe the successful management of extensive and severely contaminated facial trauma in a 22-year-old woman who sustained severely contaminated facial lacerations, partial lip avulsion, and a complex mandibular fracture after a bicycle accident. The treatment involved rigid fracture fixation, wound debridement, and primary closure under general anesthesia. After 22 months, the patient showed good healing with no nerve paralysis. Unfortunately, nasal synechiae and a hypertrophic scar in the perioral region persist. This case emphasizes the importance of timely and comprehensive management of complex facial trauma. The use of local and systemic antibiotics is crucial for infection control. Complex facial soft tissue traumas inevitably lead to scar formation, making the need for plastic revision expected.